3 - Care for Older Persons in Cameroon: Alternatives for Social Development - Ngere Nangia, Ethel (Africa Development, 2021)
Care increasingly remains a crucial facet in the lives of older persons in Africa including Cameroon. Despite its relevance to social development, providing apposite and effective care services to elderly men and women is still a major challenge in contemporary Cameroon. This is largely due to the weak institutional support system and poverty which estranges the elderly and jeopardizes their well-being. Deconstructing the current care system through the redesigning and implementation of age-friendly policies will create substantial opportunities that will predispose the old, irrespective of gender, to valued choices and better quality lives. This article describes the challenges experienced by the aged and examines the Cameroonian institutional framework for care with alternatives for social development. The article involved thirty-one elderly persons and employed an ethnographic survey design with interviews, focus group discussions, participant observation and documentary sources as instruments. Data was analysed qualitatively and the findings show that in as much as organizing the system from a multi-sectorial approach is imperative, the voices of the elderly and the consi tent provision of basic needs are also strategic to their social development.